HYDROXYCINNAMIC ACIDS INFLUENCE ON CEREBRAL CIRCULATION SYSTEM - M. N. Ivashev; R. E. Chuklin (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Increasing attention is being given in the official medicine use of plant origin for the prevention and treatment of early stages of disorders of the cardiovascular system, including oxycinnamic acids. The flow rate of cerebral blood flow were recorded by the standard method using hydrogen clearance implanted platinum elec-trodes placed on the surface of brain sagittal sinus drain region in the sinuses. Caffeic and ferulic acid in the course application significantly increase the level of cerebral blood flow rate in the animals in the experimental rules. Caffeic and ferulic acid at course prophylactic use for 14 days significantly reduced the severity of cere-brovascular pathological phenomena (hyperperfusion and hypoperfusion), which significantly reduces the risk of tissue edema of the nervous system during the first phase - hyperperfusion and also reduces the mortality rate of animals during the second phase - hypoperfusion.